THE GLOBALIZED TREATMENT OF HUMAN TRAFFICKING IN INTERNATIONAL LAW O TRATAMENTO GLOBALIZADO DO TRÁFICO DE PESSOAS NO DIREITO INTERNACIONAL - Amaral, Ana Paula Martins; Chaves, Marlon Ricardo Lima (Caderno de Relações Internacionais, 2019)
The trafficking in persons is a problem that directly affects the freedom and dignity of human beings. The globalization and transnationality inherent in this type of crime aggravates this problem and its suppression becomes more difficult. This paper aims to answer whether international human rights treaties can contribute effectively to combat this crime. Firstly, the basic concepts of globalization and trafficking in persons are presented, followed by forms of creating international treaties with their impact on public policies. Finally, an analysis of these policies in the light of the Supplementing Protocol to the United Nations Convention against Transnational Organized Crime on the Prevention, Suppression and Punishment of Trafficking in Persons, especially Women and Children, with a consequent survey of the international treaties on the subject is made. The method used was the exploratory descriptive. It was concluded that trafficking in persons is a complex phenomenon and international cooperation made through legislation contributes to enable countries in the pursuit of a more effective form of combat.